2003
DOI: 10.1167/iovs.03-0038
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Depletion Diminishes Lesion Size and Severity in Experimental Choroidal Neovascularization

Abstract: Macrophage depletion using CL(2)MDP-lip reduces size, cellularity, and vascularity of CNV. This observation supports the hypothesis that macrophages contribute to the severity of CNV lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
288
1
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 357 publications
(312 citation statements)
references
References 33 publications
18
288
1
5
Order By: Relevance
“…It has been reported that up-regulated macrophage and inflammatory cell function may worsen or exacerbate already existing inflammatory lesions [Espinosa-Heidmann et al, 2003]. This up-regulation can be spurred by both CCL2 and VEGF expression.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that up-regulated macrophage and inflammatory cell function may worsen or exacerbate already existing inflammatory lesions [Espinosa-Heidmann et al, 2003]. This up-regulation can be spurred by both CCL2 and VEGF expression.…”
Section: Discussionmentioning
confidence: 99%
“…Although the molecular bases of these diseases may be diverse, the deposits contain many shared molecular constituents that are attributable, in part, to local inflammation and activation of the complement cascade, a key element of the innate immune system in host defense. Drusen are the hallmark deposits associated with early AMD (eAMD), and recent studies have implicated local inflammation and activation of the complement cascade in their formation (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Drusen contain complement activators, inhibitors, activation-specific complement fragments, and terminal pathway components, including the membrane attack complex (MAC).…”
mentioning
confidence: 99%
“…Finally, do the conflicting results of previous studies of the role of macrophages in various models of NVAMD accurately mimic the disease in humans? [95][96][97][98] TGF-β is a multi-functional cytokine and is usually secreted in its latent form, thus allowing for sustained release throughout the repair process. 76 It can both stimulate and inhibit mitogenesis and stimulate angiogenesis, fibroblast differentiation, and matrix deposition.…”
Section: Subretinal Neovascularisationmentioning
confidence: 99%